The ROI of human capital : measuring the economic value of employee performance - Fitz-enz, Jac (AMACOM, 2000)
"The ROI of Human Capital draws on years of quantitative and qualitative international research by the Saratoga Institute to provide a methodology for measuring the bottom-line effect of employee performance. Its author, Institute founder Jac Fitz-enz, virtually invented human performance benchmarking - a concept that demands to be understood as businesses face a long-range shortage of qualified workers at all levels." "Applying a blend of management expertise and quantitative metrics, Fitz-enz shows how to build pathways that link specific human resources objectives to operational improvements and corporate financial gains. Whether you are a top executive, line manager, or HR professional, you'll learn how to gauge human costs and improve productivity at three essential levels." "The ROI of Human Capital shows how to integrate these levels into a single, end-to-end system of human capital valuation reporting. It also helps you weigh the potential effects of such practices as HR restructuring, outsourcing, using contingent workers, and merging with or acquiring another company. And, you will learn to create futures scorecards that can improve your ability to see over the horizon and far beyond your competition. Throughout, Fitz-enz enlivens his wealth of hard data with useful examples and a conversational, easy-to-read style."--Jacket